Alkali-activated porous carbon and preparation method thereof

By using alkali activation method in the preparation of porous carbon materials, the pore structure and specific surface area are regulated, and the problem of low preparation efficiency of porous carbon materials is solved, and efficient and low-cost preparation of porous carbon materials is achieved, which is suitable for the preparation of silicon carbon negative electrodes with silane deposition. Material.

CN119143127APending Publication Date: 2024-12-17CHENGDU EMINENT NEW ENERGY TECH CO LTD +2
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411549236.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, the preparation efficiency of porous carbon materials is not high, and it is difficult to achieve a reasonable pore structure and pore distribution, which affects its performance in preparing silicon carbon anode materials during silane deposition.

Method used

By mixing the matrix carbon with strong alkaline substances uniformly in the mixer at a specific mass ratio, high temperature calcination and cooling treatments were performed, and rinsing with deionized water and soaking to regulate the specific surface area and pore structure of the material, finally in the Baking at a pH-based drying to prepare alkali-activated porous carbon.

Benefits of technology

The specific surface area and pore size of porous carbon materials are controlled, the preparation steps are simple, the cost is low, and economical benefits and large-scale application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143127A_ABST
    Figure CN119143127A_ABST
Patent Text Reader

Abstract

The invention discloses alkali-activated porous carbon and a preparation method thereof, and relates to the field of new material preparation, and the preparation method comprises the following steps: uniformly mixing matrix carbon and a strong alkaline substance according to a mass ratio to obtain a mixed material, putting the mixed material into a crucible, and carrying out high-temperature calcination and cooling on the mixed material under the protection of an inert atmosphere; washing and filtering the mixed material subjected to high-temperature calcination for 3-6 times by using deionized water; after washing is completed, strong acid is used for soaking; and after soaking, filtering to obtain a mixed material filter cake, soaking the mixed material filter cake in ionized water, repeatedly washing, and drying until the pH value is neutral. The porous carbon material is prepared through alkali activation, the preparation steps are simple, expensive auxiliary equipment is not needed, the cost is low, preparation is safe, and the method has extremely high economic benefits and large-scale application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new material preparation, and in particular to alkali-activated porous carbon and a preparation method thereof. Background Art

[0002] With the rapid development of new energy battery field, higher requirements are put forward for high specific energy electrode materials. Silicon-based negative electrode materials are considered to be the most promising negative electrode materials in the field of new energy technology because of their theoretical specific capacity of up to 4200mAh / g. Driven by the joint efforts of colleagues in industry and academia, the first generation of silicon-carbon negative electrode materials mainly prepare silicon-carbon negative electrode materials by CVD coating of nano-silicon powder, the second generation of silicon-carbon negative electrode materials CVD coating of silicon oxide, and the third generation of silicon-carbon negative electrode materials pre-lithiation or pre-magnesiation of silicon oxide, and then CVD coating again. However, in actual applications, the cycle stability and discharge specific capacity of the silicon-carbon negative electrode materials prepared by the above three generations of process routes have not been effectively exerted.

[0003] In recent years, the preparation of gas-phase silicon-carbon negative electrode materials by silane cracking and deposition on the surface of porous carbon materials has become a development trend of the fourth generation of silicon-based negative electrode materials recognized by academia and industry, and thus has ushered in the rapid development of porous carbon materials. But it also brings the same development problems. For example, how to prepare porous carbon materials so that they have a reasonable pore structure, pore distribution and pore size to meet the standard requirements of uniform silane deposition, and at the same time meet the requirements of simple preparation, low cost, and large-scale mass production for batch application. For the porous carbon material industry, it is still in its infancy and has a large space for research and development.

[0004] At present, porous carbon materials are mainly prepared by methods such as water vapor activation and alkali activation. The alkali activation method mainly uses potassium hydroxide or sodium hydroxide to mix with carbon materials in a certain mass ratio and then carbonize at high temperature. How to select suitable carbon-based materials as porous carbon aggregates and what high-temperature calcination processing route to use so that the porous carbon materials can achieve a reasonable crystal phase transformation during the heat treatment process and form a stable carbon skeleton structure, there is no clear research report. From the current research conclusions of gas-phase silicon carbon, it is concluded that silane deposition of porous carbon can be used to prepare silicon-carbon negative electrode materials. The requirements for porous carbon are that the specific surface area is ≥1500 m2 / g, the pore volume is ≥0.8cm3 / g, and the pore size is mainly micropores, between 2~3nm.

[0005] Therefore, how to achieve efficient preparation of porous carbon materials and ensure a certain specific surface area, pore volume and pore diameter that can be used for silane deposition to prepare silicon-carbon negative electrode materials is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing alkali-activated porous carbon, so as to solve the problem of low preparation efficiency of porous carbon materials in the prior art.

[0007] The present invention is achieved by the following technical scheme, a method for preparing alkali-activated porous carbon, characterized in that the preparation method comprises adding matrix carbon and strong alkaline substance into a mixer in a mass ratio of 0.5 to 1:5 and uniformly mixing to obtain a mixed material, wherein the mixer speed is 200 to 600 rpm, the mixing time is 3 to 30 minutes; the mixed material is placed in a crucible, and the mixed material is calcined at high temperature and cooled in an inert gas environment, wherein the crucible is one of a graphite crucible, a corundum crucible, and a ceramic crucible; the mixed material after high-temperature calcination is rinsed with deionized water, wherein the rinsing includes completely dispersing the calcined mixed material in deionized water, and rinsing and filtering the mixed material 3 to 6 times with deionized water; after rinsing, the mixed material is soaked in a strong acid with a concentration of 0.5 mol / L to 9 mol / L, and the soaking time is 2 to 8 hours, wherein the strong acid is any one of hydrochloric acid or nitric acid; after soaking, the mixed material filter cake is obtained by filtering, and the mixed material filter cake is soaked in ionized water and rinsed repeatedly until the pH value is neutral and then dried.

[0008] Further, the matrix carbon includes a combination of one or more of biomass-based carbon, resin-based carbon and petroleum coke-based carbon.

[0009] Furthermore, the strong alkaline substance includes one of sodium hydroxide or potassium hydroxide or a combination of both.

[0010] Furthermore, the mass ratio of the combination of the sodium hydroxide or potassium hydroxide is 0.1~1:1.

[0011] Furthermore, the gas of the inert atmosphere is any one of nitrogen, helium, neon, argon, krypton and xenon, or a combination of two thereof, and the oxygen content is maintained at ≤25ppm in the inert gas environment.

[0012] Furthermore, the high-temperature calcination includes two calcination processes and two cooling processes, wherein the two calcination processes are as follows: the first heating process is to heat the temperature from 25°C to 450~650°C at a heating rate of 2~15°C / min, and keep the constant temperature for 0.5~2h after heating to 450~650°C, and the flow rate of the inert gas is 3~15 L / min; the second heating process is to heat the temperature from 450~650°C to 800~1000°C at a heating rate of 2~15°C / min, and keep the constant temperature for 0.5~6h after heating to 800~1000°C, and the flow rate of the inert gas is 3~15 L / min; the two cooling processes are as follows: the first cooling process is to reduce the temperature from 800°C~1000°C to 500°C~600°C at a cooling rate of 20~50°C / h, and the flow rate of the inert gas is 3~15 L / min; the second cooling process is from 500℃~600℃ to 25℃ at a cooling rate of 30~90℃ / h, and the flow rate of inert gas is 5~25 L / min.

[0013] Furthermore, drying includes using a vacuum drying oven or a blast drying oven for drying, the drying temperature is 100° C. to 150° C., and the drying time is 2 to 6 hours.

[0014] Furthermore, the biomass-based carbon includes one or more combinations of carbons obtained by carbonizing corn stalks, apricot shells, coconut shells, walnut shells, wood chips, bamboo, and sugarcane bagasse; the volatile matter content of the biomass-based carbon is 10-15wt%.

[0015] Furthermore, the resin-based carbon includes one or more combinations of carbons obtained by directly carbonizing thermosetting phenolic resins, epoxy resins, furan resins, polyimide resins, polyurethane resins, and polyamide resins.

[0016] Furthermore, the petroleum coke-based carbon includes a combination of one or more of petroleum coke, needle coke, calcined coke and pitch coke-based carbon, and the volatile matter content of the petroleum coke-based carbon is 5-12wt%.

[0017] Another aspect of the present invention provides an alkali-activated porous carbon. The alkali-activated porous carbon material is prepared according to the method described above.

[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0019] The present invention prepares porous carbon materials through alkali activation, and the finally obtained porous carbon has a specific surface area, pore size and pore volume that can be regulated. At the same time, the preparation steps are simple, no expensive auxiliary equipment is required, the cost is low, the preparation is safe, and it has extremely strong economic benefits and large-scale application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0021] Figure 1 This is a flow chart of the preparation method of Example 1 of the present invention.

[0022] Figure 2 This is a scanning electron microscope image of the biomass-based porous carbon material of Example 2 of the present invention.

[0023] Figure 3 This is a nitrogen isothermal adsorption-desorption curve diagram of the biomass-based porous carbon material of Example 2 of the present invention.

[0024] Figure 4 This is a pore volume-pore size distribution diagram of the biomass-based porous carbon material of Example 2 of the present invention.

[0025] Figure 5 This is the XRD diagram of the biomass-based porous carbon material of Example 2 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0027] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art in the art to which the present invention relates. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail. Regarding the "comprising", "including", "having", "containing", etc. used herein, they are all open-ended terms, that is, they mean including but not limited to. Unless the context clearly indicates otherwise, the expressions "a" and "one" used herein include plural references. For example, referring to "a cell" includes a plurality of such cells and equivalents known to those skilled in the art, etc. The term "about" used herein means a range of ±20% of the value thereafter. In some embodiments, the term "about" means a range of ±10% of the value thereafter. In some embodiments, the term "about" means a range of ±5% of the value thereafter.

[0028] Embodiment 1,

[0029] Figure 1The method flow chart of this exemplary embodiment is shown, and this exemplary embodiment provides a method for preparing alkali-activated porous carbon. Specifically, it includes the following steps:

[0030] Step 1: Add the matrix carbon and the strong alkaline substance into a mixer at a mass ratio of 0.5:5 and mix them evenly to obtain a mixed material. The mixer speed is 200 rpm and the mixing time is 3 minutes.

[0031] Specifically, the matrix carbon may include a combination of one or more of biomass-based carbon, resin-based carbon, and petroleum coke-based carbon. The biomass-based carbon may include a combination of one or more of carbon obtained by carbonizing corn stalks, apricot shells, coconut shells, walnut shells, sawdust, bamboo, and sugarcane bagasse; and the volatile matter content of the biomass-based carbon is 10-15wt%.

[0032] The resin-based carbon includes one or more combinations of carbons obtained by directly carbonizing thermosetting phenolic resins, epoxy resins, furan resins, polyimide resins, polyurethane resins, and polyamide resins.

[0033] The petroleum coke-based carbon includes a combination of one or more of petroleum coke, needle coke, calcined coke and pitch coke-based carbon, and the volatile matter content of the petroleum coke-based carbon is 5-12wt%.

[0034] In this embodiment, the strong alkaline substance in step 1 includes sodium hydroxide or potassium hydroxide or a combination of the two. The mass ratio of the combination of sodium hydroxide and potassium hydroxide is 0.1-1:1.

[0035] It should be noted that sodium hydroxide also has the function of etching carbon-based materials, and the market price of alkaline substance potassium hydroxide is about 2 to 3 times that of sodium hydroxide. How to optimize the quality of the two groups of alkaline substances according to a certain ratio and through a certain process route experiment to maintain the stability of porous carbon performance and ensure the lowest cost, there are no more research conclusions. In addition, since alkaline materials are highly corrosive to equipment, adding sodium hydroxide with slightly lower alkalinity instead of potassium hydroxide can also effectively increase the service life of the equipment.

[0036] Step 2: Put the mixed material into a crucible, and calcine the mixed material at high temperature and cool it down under the protection of an inert atmosphere. In this embodiment, the crucible used can be a graphite crucible, a corundum crucible or a ceramic crucible.

[0037] In this embodiment, the gas of the inert atmosphere can be any one of nitrogen, helium, neon, argon, krypton, and xenon, or a combination of two thereof. The oxygen content in the inert atmosphere should be maintained at ≤25 ppm.

[0038] Step 3: Use deionized water to rinse the mixed material after high-temperature calcination. The rinsing includes completely dispersing the calcined mixed material in deionized water, and rinsing and filtering with deionized water for 3 times.

[0039] Specifically, the high temperature calcination includes two stages of calcination and two stages of cooling process.

[0040] Among them, the two-stage calcination process is: the first stage of the heating process is from 25°C to 450°C, the heating rate is 2°C / min, and the temperature is kept constant for 2 hours after heating to 450°C, and the flow rate of the inert gas is 15 L / min; the second stage of the heating process is from 450°C to 800°C, the heating rate is 2°C / min, and the temperature is kept constant for 6 hours after heating to 800°C, and the flow rate of the inert gas is 15 L / min.

[0041] The two-stage cooling process is:

[0042] In the first cooling process, the temperature was reduced from 800°C to 500°C at a cooling rate of 20°C / h, and the flow rate of the inert gas was 3 L / min. In the second cooling process, the temperature was reduced from 500°C to 25°C at a cooling rate of 30°C / h, and the flow rate of the inert gas was 25 L / min.

[0043] Step 4: After rinsing, soak in a strong acid with a concentration of 0.5 mol / L for 8 hours. In this embodiment, the strong acid can be either hydrochloric acid or nitric acid.

[0044] Step 5: After the soaking is completed, the mixture is filtered to obtain a filter cake, and the filter cake is soaked in deionized water and repeatedly rinsed until the pH value is neutral and then dried.

[0045] Specifically, a vacuum drying oven or a blast drying oven can be used for drying, the drying temperature is 100° C., and the drying time is 6 hours.

[0046] Embodiment 2,

[0047] In this embodiment, a method for preparing alkali-activated porous carbon is provided. The activated porous carbon is finally obtained through the steps described. Figure 2 The scanning electron microscope image of the alkali-activated porous carbon prepared by the method steps of this embodiment is shown. The preparation steps include the following:

[0048] Step 1: Weigh about 150g of biomass coconut shell charcoal, the particle size is about: D0 1.5μm, D10 4.7μm, D50 8.7μm, D100 28.3μm. Weigh 450g of potassium hydroxide (KOH), evacuate in a high-speed mixer (vacuum degree ≤ 50kpa), and mix at a speed of 400rpm for 10 min to obtain a uniformly mixed material, marked as sample A.

[0049] Step 2: Place sample A in a graphite crucible with a length*width*height of 35*25*15 cm respectively, and place it in the middle heating zone of a high-temperature tube furnace for high-temperature heat treatment.

[0050] Step 3: Pass nitrogen for 30 minutes at a nitrogen flow rate of 10L / min to exclude air from the high-temperature sintering furnace to prevent oxidation of the material. After the air is excluded, start the heating program at a heating rate of 5℃ / min until the temperature reaches 500℃. Stop heating and keep the temperature constant for 1h, then maintain the gas flow rate at 10L / min, slowly heat up at a heating rate of 3℃ / min until the material temperature reaches 850℃, and keep the temperature constant for 2h. During the cooling process, cool from 850℃ to 500℃, maintain the gas flow rate at 10 L / min, cool slowly, and keep the cooling rate at 50℃ / h. When the temperature drops to about 500℃, adjust the gas flow rate to 15 L / min until it cools to room temperature, take it out of the furnace, and mark it as sample B. Figure 3 The isothermal adsorption-desorption curve of nitrogen in this example is shown.

[0051] Step 4: Take out sample B and add sufficient deionized water to completely disperse the material in the deionized water until no lumps appear. Continue to rinse with deionized water, filter 5 times to remove more alkali metal elements, and mark it as sample C.

[0052] Step 5: Take out sample C, soak it in 6 mol / L dilute hydrochloric acid for 6 hours while stirring, and then filter it. After the filtration is completed, the material is marked as sample D.

[0053] Step 6: Continue to soak sample D in deionized water and rinse repeatedly until the pH value is neutral. Mark it as sample E.

[0054] Step 7: Dry sample E in a vacuum drying oven at 120°C for 5 hours to obtain a porous carbon material. Figure 4 The pore volume-pore size distribution diagram of the biomass-based porous carbon material of this embodiment is shown; Figure 5 The XRD pattern of the biomass-based porous carbon material of this example is shown.

[0055] Embodiment 3,

[0056] This embodiment provides an alkali activation method for preparing porous carbon materials. Unlike Example 2, the carbon-based material in this embodiment is biomass-based coconut shell charcoal, and the alkaline substance is pure sodium hydroxide (NaOH), with a mass of 450 g. The remaining raw materials are consistent with those in Implementation Case 1, and the remaining experimental steps and operations are carried out according to those in Implementation Case 2.

[0057] Embodiment 4,

[0058] This embodiment provides an alkali activation method for preparing porous carbon materials. Unlike Example 2, the carbon-based material in this embodiment is biomass-based coconut shell charcoal, and the alkaline substance is a mixed alkaline substance in which potassium hydroxide and sodium hydroxide are evenly mixed in a ratio of 1:1, and the masses are 225g potassium hydroxide (KOH) and 225g sodium hydroxide (NaOH). The remaining raw materials are the same as those in Implementation Case 2, the mass of the added coconut shell charcoal remains unchanged at 150g, and the remaining steps are carried out according to Implementation Case 2.

[0059] Embodiment 5,

[0060] This embodiment provides an alkali activation method for preparing a porous carbon material. Different from Embodiment 2, the carbon-based material in this embodiment is phenolic resin-based carbon, which specifically includes the following steps:

[0061] Step 1: Use a grinder to crush the phenolic resin into particles with a D50 of 15-20 μm, put them into a graphite crucible, and mark them as sample A.

[0062] Step 2: Place sample A in a high-temperature tubular furnace for carbonization treatment. Under a nitrogen flow rate of 10 L / min, pre-exhaust the air in the tubular furnace for 15 minutes, and then start the heating program. The heating curve is: from room temperature to 500°C, the heating rate is 5°C / min, and the temperature is kept constant for 4 hours until the phenolic resin is completely carbonized. After cooling to room temperature, take the material out of the high-temperature tubular furnace and mark it as sample B.

[0063] Step 3: Weigh the carbonized phenolic resin (150 g), 225 g potassium hydroxide (KOH), and 225 g sodium hydroxide (NaOH), mix them evenly, and mark them as sample C. The mixer speed is 600 rpm and the mixing time is 30 min.

[0064] Step 4: Place the mixed material into a ceramic crucible, and calcine the mixed material at high temperature and then cool it down in an argon inert atmosphere with an oxygen content of ≤25ppm.

[0065] Specifically, in this step, the high-temperature calcination process is to first carry out the first heating process, from 25°C to 650°C, with a heating rate of 15°C / min, and keep the constant temperature for 2 hours after heating to 650°C, and the flow rate of the inert gas is 15L / min.

[0066] Then the second heating process was carried out, from 650°C to 1000°C, with a heating rate of 15°C / min. After reaching 1000°C, the constant temperature was maintained for 6 hours, and the inert gas flow rate was 15 L / min.

[0067] After the high-temperature calcination is completed, two stages of cooling are carried out. First, in the first stage of cooling, the temperature is reduced from 1000°C to 600°C at a cooling rate of 50°C / h, and the flow rate of the inert gas is 15L / min.

[0068] In the second cooling process, the temperature was cooled from 600°C to 25°C at a cooling rate of 90°C / h, and the flow rate of the inert gas was 25 L / min.

[0069] Step 5: Use deionized water to rinse the mixed material after high-temperature calcination. The rinsing includes completely dispersing the calcined C sample in deionized water, and rinsing and filtering with deionized water for 6 times.

[0070] Step 6: After rinsing, soak in 7 mol / L hydrochloric acid for 8 hours.

[0071] Step 7: After soaking, the mixture is filtered to obtain a filter cake, which is soaked in deionized water and rinsed repeatedly until the pH value is neutral and then dried. In this embodiment, a vacuum drying oven is used for drying, the drying temperature is 150° C., and the drying time is 6 hours.

[0072] Embodiment 6,

[0073] This embodiment provides an alkali activation method for preparing porous carbon materials. Different from Example 2, the carbon-based material in this embodiment is asphalt, and the carbon-based material is mixed with potassium hydroxide and sodium hydroxide in a mass ratio of 2:3:3, i.e., 150g asphalt, 225g potassium hydroxide (KOH), and 225g sodium hydroxide (NaOH). Other raw materials are the same as in Example 2.

[0074] The specific steps are:

[0075] Step 1: Add 150 g of asphalt, 225 g of potassium hydroxide (KOH), and 225 g of sodium hydroxide (NaOH) into a mixer and mix them evenly to obtain a mixed material. The mixer speed is 300 rpm and the mixing time is 15 min.

[0076] Step 2: Place the mixed material into a corundum crucible and keep the oxygen content ≤ 25 ppm under the protection of neon atmosphere. Sinter the mixed material at high temperature and cool it down. In this embodiment, the crucible used can be a graphite crucible, a corundum crucible or a ceramic crucible.

[0077] Step 3: Use deionized water to rinse the mixed material after high-temperature calcination. The rinsing includes completely dispersing the calcined mixed material in deionized water, and rinsing and filtering with deionized water for 5 times.

[0078] In this embodiment, high temperature calcination includes firstly heating from 25°C to 500°C at a heating rate of 10°C / min, and then maintaining the temperature at 500°C for 1 hour, with the flow rate of the inert gas being 9 L / min.

[0079] Then the temperature was raised from 500°C to 900°C at a heating rate of 10°C / min. After reaching 900°C, the temperature was kept constant for 3 h, and the inert gas flow rate was 9 L / min.

[0080] After the above heating step is completed, the temperature is cooled. The specific process is as follows: first, the temperature is reduced from 900°C to 550°C at a cooling rate of 30°C / h, and the flow rate of the inert gas is 9 L / min.

[0081] Then, the temperature was cooled from 500 °C to 25 °C at a cooling rate of 40 °C / h, and the flow rate of the inert gas was 5~25 L / min.

[0082] Step 4: After rinsing, soak in 6 mol / L nitric acid for 2 hours.

[0083] Step 5: After the soaking is completed, the mixture is filtered to obtain a filter cake, and the filter cake is soaked in deionized water and rinsed repeatedly until the pH value is neutral, and then dried in a forced air drying oven at a drying temperature of 120° C. for 3 hours.

[0084] Embodiment 7,

[0085] This embodiment provides an alkali activation method for preparing porous carbon materials. Different from Example 2, the carbon-based material in this embodiment is needle coke, and the carbon-based material is mixed with potassium hydroxide and sodium hydroxide in a mass ratio of 2:3:3, i.e., 150 g of asphalt, 225 g of potassium hydroxide (KOH), and 225 g of sodium hydroxide (NaOH). Other raw materials are the same as in the steps and Example 6.

[0086] The test results of the porous carbon materials prepared in Examples 2 to 7 are shown in Table 1.

[0087] Table 1. Test results of porous carbon materials

[0088]

[0089] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing alkali-activated porous carbon, It is characterized in that The preparation method comprises: Add the matrix carbon and the strong alkaline substance into the mixer at a mass ratio of 0.5-1:5 and mix them evenly to obtain a mixed material. Among them, the mixer speed is 200~600 rpm, and the mixing time is 3~30min; The mixed material is placed in a crucible, and the mixed material is calcined at high temperature and cooled down in an inert gas environment, wherein the crucible is one of a graphite crucible, a corundum crucible, and a ceramic crucible; The mixed material after high-temperature calcination is rinsed with deionized water, wherein the rinsing includes completely dispersing the calcined mixed material in deionized water, and rinsing and filtering the mixed material 3 to 6 times with deionized water; After the rinsing is completed, the mixed material is soaked in a strong acid with a concentration of 0.5 mol / L to 9 mol / L for 2 to 8 hours. The strong acid is any one of hydrochloric acid or nitric acid. After the soaking is completed, the mixture is filtered to obtain a filter cake, which is then soaked in ionized water and rinsed repeatedly until the pH value is neutral and then dried.

2. The method for preparing alkali-activated porous carbon according to claim 1, It is characterized in that The matrix carbon includes one or more combinations of biomass-based carbon, resin-based carbon and petroleum coke-based carbon.

3. The method for preparing alkali-activated porous carbon according to claim 1, It is characterized in that The strong alkaline substance includes sodium hydroxide or potassium hydroxide or a combination of the two.

4. The method for preparing alkali-activated porous carbon according to claim 1, It is characterized in that The gas of the inert atmosphere is any one of nitrogen, helium, neon, argon, krypton and xenon, or a combination of two thereof, and the oxygen content is maintained at ≤25 ppm in the inert gas environment.

5. The method for preparing alkali-activated porous carbon according to claim 1, It is characterized in that The high temperature calcination includes two stages of calcination and two stages of cooling process, wherein: The two-stage calcination process is: The first stage of heating process is from 25℃ to 450~650℃, the heating rate is 2~15℃ / min, the temperature is kept constant for 0.5~2h after reaching 450~650℃, and the flow rate of inert gas is 3~15L / min; The second stage of heating process is from 450~650℃ to 800~1000℃, the heating rate is 2~15℃ / min, after heating to 800~1000℃, the constant temperature time is 0.5~6h, and the inert gas flow rate is 3~15L / min; The two-stage cooling process is: In the first cooling process, the temperature is reduced from 800℃~1000℃ to 500℃~600℃ at a cooling rate of 20~50℃ / h, and the flow rate of inert gas is 3~15L / min; The second cooling process is from 500℃~600℃ to 25℃ at a cooling rate of 30~90℃ / h, and the flow rate of inert gas is 5~25L / min.

6. The method for preparing alkali-activated porous carbon according to claim 1, It is characterized in that The drying includes using a vacuum drying oven or a blast drying oven for drying, the drying temperature is 100° C. to 150° C., and the drying time is 2 to 6 hours.

7. The method for preparing alkali-activated porous carbon according to claim 2, It is characterized in that The biomass-based carbon includes one or more combinations of carbons obtained by carbonizing corn stalks, apricot shells, coconut shells, walnut shells, wood chips, bamboo and sugarcane bagasse; the volatile matter content of the biomass-based carbon is 10-15wt%.

8. The method for preparing alkali-activated porous carbon according to claim 2, It is characterized in that The resin-based carbon includes one or more combinations of carbons obtained by directly carbonizing thermosetting phenolic resin, epoxy resin, furan resin, polyimide resin, polyurethane resin and polyamide resin.

9. The method for preparing alkali-activated porous carbon according to claim 2, It is characterized in that The petroleum coke-based carbon includes a combination of one or more of petroleum coke, needle coke, calcined coke and pitch coke-based carbon, and the volatile matter content of the petroleum coke-based carbon is 5-12wt%.

10. An alkali-activated porous carbon, It is characterized in that The alkali-activated porous carbon is prepared according to the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Method for preparing porous carbon by using humin

    CN120208230A

  • Composite TiC porous carbon as well as preparation method and application thereof

    CN120841514A

  • Preparation process of bamboo-based biochar for artificial aggregate

    CN121134742A

  • Asphalt-based porous carbon and preparation method thereof

    CN121757864A